Epidemiological features and spatial-temporal clustering of visceral leishmaniasis in mainland China from 2019 to 2021 - Li, Yuanyuan; Luo, Zhuowei; Hao, Yuwan; Zhang, Yi; Yang, Limin; Li, Zhongqiu; Zhou, Zhengbin; Li, Shizhu (Frontiers in Microbiology, 2022)
Background: Visceral leishmaniasis (VL) is seriously vector-borne disease in the central and western China. Recent years, the number of VL cases increased gradually, especially mountain-type zoonotic visceral leishmaniasis (MT-ZVL). The purpose of this study is to clarify the epidemiological features and spatial-temporal clustering of VL in China between 2019 and 2021, so as to provide insights into VL prevention and control. Methods: The information of VL cases in 2019-2021 was collected from the Infectious Disease Reporting Information Management System of the Chinese Center for Disease Control and Prevention. Epidemiology characteristics analysis of VL cases was described.The global Moran's I and Getis-ORD Gi* statistical data were processed for spatial autocorrelation and hotspot analysis in ESRI ArcGIS software. And spatial-temporal clustering analysis was conducted with the retrospective space-time permutation scan statistics. Results: A total of 608 VL cases were reported from 2019 to 2021, with 158, 213 and 237 cases reported each year respectively. And including 10 cases of anthroponotic visceral leishmaniasis (AVL), 20 cases of desert-type zoonotic visceral leishmaniasis (DT-ZVL) and 578 cases of MT-ZVL. The age of VL cases was mainly distributed in the group of ≥15 years old. Peasants and infants are the dominated high risk population. The incidence peak of VL occurred between March and May. The cases were mainly distributed in Shanxi (299 cases), Shaanxi (118 cases) and Gansu (106 cases) Provinces. Spatial analysis revealed that clustering of infection mainly located in eastern of Shanxi province and Shaanxi-Shanxi border areas, as well as southern Gansu and northern Sichuan Province. In addition, new reemergence hotspots in Shanxi, Henan and Hebei Province were detected since 2020. Spatiotemporal clustering analysis revealed an increase in the degree of infection aggregation in eastern of Shanxi province and Shaanxi-Shanxi border areas. Conclusions: The AVL and DT-ZVL were endemic at a lower lever in China, whereas, MT-ZVL has rebounded rapidly and resurgence in historically-endemic counties. The spatial-temporal clustering analysis displayed that the high incidence areas of VL has shifted to central China especially in Shanxi and Shaanxi provinces. Integrated mitigation strategies targeting high-risk population are needed to control VL transmission in high-risk areas.